Website Development Training for Batik Entrepreneurs in Kampung Wisata Batik Pesindon - Nasution, Nur Baiti; Wibowo, Dwi Edi; Sunarjo, Wenti Ayu; Sasongko, Aditya Dimas Wahyu; Rabbani, Nauval; Hartanto, Dwi (LPPM Universitas Timor, 2024)
A website is a digital marketing tool for any enterprise, especially in today's digital era where every company should have its own website. However, most batik shops in Kampung Wisata Batik Pesindon (KWBP) still do not have a website. The objective of this community service was to develop websites for 17 batik shops in KWBP and then provide training on how to fill and update these websites. The community service were carried out in five stages: problem identification, pre-training, training, mentoring, and monitoring and evaluation. Problem identification is conducted through interviews regarding the desired website needs. Pre-training involves creating websites for the 17 batik shops and one large website for KWBP. The training stage was conducted through demonstration and hands-on practice. Mentoring was done using a WhatsApp group, and evaluation was performed using observation sheets of training results. Based on the results, it was found that this activity can improve partners' skills in website content filling by 59% and increase partners' accessibility to website technology by 100%. The challenge encountered during training was that partners have not prepared the necessary website assets such as the batik shop logo and uploaded product images. However, overall, the participants' enthusiasm was considered high.